A rare occurrence of pyloric stenosis in an infant with osteogenesis imperfecta: Anesthetic implications - Sheetal R Jagtap; Rochana G Bakhshi; Ankit Jain (Wolters Kluwer Medknow Publications, 2014)
Congenital anomalies pose many challenges during anesthesia due to anatomic and physiological alterations. The inherent complications associated with the disorders necessitate vigilance for providing anesthesia to even seemingly simple surgical intervention. Here, we share our experience of anesthesia management of an infant of congenital osteogenesis imperfecta with pyloric stenosis for pyloromyotomy.